2015
DOI: 10.1016/j.resuscitation.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Can binary early warning scores perform as well as standard early warning scores for discriminating a patient's risk of cardiac arrest, death or unanticipated intensive care unit admission?

Abstract: The performance of Binary NEWS is only exceeded by that of standard NEWS. It may be that Binary NEWS, as a simplified system, can be used with fewer errors. However, its introduction could lead to significant increases in workload for ward and rapid response team staff. The balance between fewer errors and a potentially greater workload needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…EWS are physiological scoring systems based on a rapid and quantitative assessment of changes in vital signs, 7 and were initially developed to identify and track hospitalised patients at risk of deterioration outside critical care areas in order to ensure early stabilisation and transfer to intensive care unit (ICU) when appropriate, and to prevent avoidable cardiac arrests. 8 , 9 However, these scores have also subsequently been investigated as a tool to predict critical illness in ED patients, 10 and some, as the Rapid Emergency Medicine Score (REMS), 11 have specifically been developed for this purpose. In studies performed on the general ED population, the National Early Warning Score (NEWS) 12 was the most accurate in predicting both in-hospital mortality and ICU admission.…”
Section: Introductionmentioning
confidence: 99%
“…EWS are physiological scoring systems based on a rapid and quantitative assessment of changes in vital signs, 7 and were initially developed to identify and track hospitalised patients at risk of deterioration outside critical care areas in order to ensure early stabilisation and transfer to intensive care unit (ICU) when appropriate, and to prevent avoidable cardiac arrests. 8 , 9 However, these scores have also subsequently been investigated as a tool to predict critical illness in ED patients, 10 and some, as the Rapid Emergency Medicine Score (REMS), 11 have specifically been developed for this purpose. In studies performed on the general ED population, the National Early Warning Score (NEWS) 12 was the most accurate in predicting both in-hospital mortality and ICU admission.…”
Section: Introductionmentioning
confidence: 99%
“…Scoring errors tend to cause underscoring as demonstrated by Smith et al during an epidemic of Legionnaire's disease (17). Particularly in those patients seemingly 'well' , erroneous recordings may increase, especially when nurses refrain from manually counting the respiratory rate (16). This 'well-patient bias' might lead to underscoring and skipping of the deteriorating patient, which might also be the case with the single patient who died but did not have a high score recording; she was admitted as an elective case from the outpatient clinic because of joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…To add weight to this suggestion a further study evaluated the weightings and calculations used for early warning scores (EWS) where calculation errors may potentially impact on hospital efficiency and patient care. 20 They truncated 36 published 'standard' EWSs so that, for each component, only two scores were possible: 0 when the standard EWS scored 0 and 1 when the standard EWS scored greater than 0. They found that binary EWSs had lower Area under the Receiver Operating Characteristics (AUROCs) than the standard EWSs in most cases, although for some the difference was not significant.…”
Section: Rapid Response Systemsmentioning
confidence: 99%